Lipidated Calcitonin Gene-Related Peptide (CGRP) Peptide Antagonists Retain CGRP Receptor Activity and Attenuate CGRP Action In Vivo - Jamaluddin, Aqfan; Chuang, Chia-Lin; Williams, Elyse T.; Siow, Andrew; Yang, Sung Hyun; Harris, Paul W. R.; Petersen, Jakeb S. S. M.; Bower, Rebekah L.; Chand, Shanan; Brimble, Margaret A.; Walker, Christopher S.; Hay, Debbie L.; et al. (Frontiers in Pharmacology, 2022)
Signaling through calcitonin gene-related peptide (CGRP) receptors is associated with pain, migraine, and energy expenditure. Small molecule and monoclonal antibody CGRP receptor antagonists that block endogenous CGRP action are in clinical use as anti-migraine therapies. By comparison, the potential utility of peptide antagonists has received less attention due to suboptimal pharmacokinetic properties. Lipidation is an established strategy to increase peptide half-life in vivo. This study aimed to explore the feasibility of developing lipidated CGRP peptide antagonists that retain receptor antagonist activity in vitro and attenuate endogenous CGRP action in vivo. CGRP peptide analogues based on the archetypal CGRP receptor antagonist, CGRP8-37, were palmitoylated at the N-terminus, position 24, and near the C-terminus at position 35. The antagonist activities of the lipidated peptide analogues were tested in vitro using transfected Cos-7 cells expressing either the human or mouse CGRP receptor, amylin subtype 1 (AMY1) receptor, adrenomedullin (AM) receptors, or calcitonin (CT) receptor. Antagonist activities were also evaluated in SK-N-MC cells that endogenously express the human CGRP receptor. Lipidated peptides were then tested for their ability to antagonize endogenous CGRP action in vivo using a capsaicin-induced dermal vasodilation (CIDV) model in C57/BL6J mice. All lipidated peptides except for the C-terminally modified analogue retained potent antagonist activity compared to CGRP8-37 towards the CGRP receptor. The lipidated peptides also retained, and sometimes gained, antagonist activities at AMY1, AM1 and AM2 receptors. Several lipidated peptides produced robust inhibition of CIDV in mice. This study demonstrates that selected lipidated peptide antagonists based on αCGRP8-37 retain potent antagonist activity at the CGRP receptor and are capable of inhibition of endogenous CGRP action in vivo. These findings suggest that lipidation can be applied to peptide antagonists, such as αCGRP8-37 and are a potential strategy for antagonizing CGRP action.